Growing Together: The Impact of the Regulation of Non-Innovative Activities on Agricultural Innovation Governance. (21st August 2017) - Ludlow, Karinne
ABSTRACT: This article focuses on one of the most hotly contested interfaces around innovation—that between the organic sector and agricultural sectors that adopt innovation, using two case studies: genetically modified crops and nanotechnology. Through an analysis of four supranational and national regulatory frameworks for organic agriculture the article demonstrates how important difficulties are caused for innovation governance by regulations meant for non-innovative activities. These difficulties adversely impact consumers and the feasibility of coexistence between innovation adopters and non-adopters. More broadly, the article demonstrates why regulatory frameworks for non-innovators should be included in innovation policy considerations.